Analysis of Postgraduate Theses on Teaching English - Tuncer, Murat; Çetin, Ezgi Yıldız (Hüdaverdi BİRCAN, 2024)
The aim of this research is to investigate the postgraduate theses on teaching English as a foreign language. For this purpose, “English” and “Teaching” were written in the “advanced search” section of the Council of Higher Education Thesis Center, and out of 147 postgraduate theses listed, 75 master’s and doctoral thesis with the subject “Education and Training” were examined. These postgraduate theses were analyzed with the help of document analysis. Considering the theses examined the mixed method was used most commonly in the researches. It was seen that the most preferred data collection tools were the questionnaires and the interview forms. It was concluded that the studies were conducted with relatively smaller groups. Convenience sampling was most frequently used as a sampling method. The results of the study showed that the common findings of the postgraduate theses on teaching English as a foreign language were obtained from the subjects related to using drama in teaching English, teaching vocabulary, and the Common European Framework of Reference for Languages (CEFR). Furthermore, it was found out that the suggestions of the postgraduate theses mostly correlated with the findings of the theses. The suggestion “The number of participants can be increased.” was the most frequently used among the suggestions correlated with the findings.

Bu araştırmanın amacı yabancı dil olarak İngilizce öğretimi ile ilgili lisansüstü tezleri çeşitli açılardan incelemektir. Bu amaç doğrultusunda Yükseköğretim Kurulu Ulusal Tez Merkezi’nin “gelişmiş tarama” kısmına “İngilizce” ve “öğretimi” yazılmış ve listelenen 147 lisansüstü tezden konusu “Eğitim ve Öğretim” olan 75 yüksek lisans ve doktora tezi incelenmiştir. Çalışma kapsamına alınan lisansüstü tezler doküman incelemesi yöntemi ile incelenmiştir. İncelenen tezler dikkate alındığında en fazla karma araştırma yönteminin kullanıldığı ve veri toplama araçlarından en çok anket ve görüşme formunun tercih edildiği görülmüştür. Araştırmalarda nispeten daha küçük gruplarla çalışıldığı sonucuna ulaşılmıştır. Örneklem seçim yöntemlerinden ise en sık uygun örnekleme tercih edilmiştir. Yabancı dil olarak İngilizce öğretimi alanında hazırlanmış lisansüstü tezlerden elde edilen ortak bulguların en çok İngilizce öğretiminde dramanın kullanılması, kelime öğretimi ve Avrupa Dilleri Ortak Çerçeve Programı konularından elde edildiği görülmüştür. Ayrıca değerlendirilen lisansüstü tezlerde yer alan önerilerin çoğunlukla bulgularla ilişkili olduğu tespit edilmiştir. Bulgularla ilişkili önerilerden en sık karşılaşılan öneri “Araştırmaya dâhil edilen katılımcı sayısı artırılabilir.” önerisidir.
İngilizce Öğretimi İle İlgili Lisansüstü Tezlerin İncelenmesi
Keywords: Cognitive and Computational Psychology (Other); Bilişsel ve Hesaplamalı Psikoloji (Diğer)